1994
DOI: 10.1523/jneurosci.14-11-06412.1994
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrate-1 (IRS-1) distribution in the rat central nervous system

Abstract: Insulin receptor substrate 1 (IRS-1) is the primary cytosolic substrate of the insulin and insulin-like growth factor-I (IGF-I) receptors. Following tyrosine phosphorylation IRS-1 binds to and activates specific proteins containing SH2 domains. Using biochemical and immunocytochemical techniques, we have mapped the distribution of IRS-1 in the CNS of the adult rat and compared it with that of insulin and IGF-I receptors and phosphatidylinositol 3-kinase (PI-3 kinase), a signaling molecule functionally related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 35 publications
4
91
1
3
Order By: Relevance
“…Our present findings further support a possible major neuromodulatory role of IGF-1 in the adult mammalian nervous system. Both IGF-1 receptor and IGF-1 are present within the SON of adult rats A maintained expression of IGF-1 receptors in adult rat SON neurons has been reported previously (Folli et al, 1994;CardonaGomez et al, 2000). We confirmed this and further showed that this receptor is present on the soma and dendrites of both OT and VP neurons, providing morphological support to our functional results.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Our present findings further support a possible major neuromodulatory role of IGF-1 in the adult mammalian nervous system. Both IGF-1 receptor and IGF-1 are present within the SON of adult rats A maintained expression of IGF-1 receptors in adult rat SON neurons has been reported previously (Folli et al, 1994;CardonaGomez et al, 2000). We confirmed this and further showed that this receptor is present on the soma and dendrites of both OT and VP neurons, providing morphological support to our functional results.…”
supporting
confidence: 52%
“…These two mechanisms act in concert to finely modulate neuronal activity Voisin and Bourque, 2002). IGF-1 immunoreactivity and mRNA have been observed in adult SON neurons (Aguado et al, 1992;Zhou et al, 1999), and high expression of the IGF-1 receptor has been reported in the SON (Folli et al, 1994;Cardona-Gomez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lesions to the hippocampus produce severe loss of learning ability and memory that can be significantly reversed by insulin treatment (De Castro and Balagura 1976;Horel 1978;Huppert and Piercy 1979;Spiers et al 2001). Both insulin receptor substrate-1 and phosphatidyinositol-3 phosphate kinase are abundantly expressed in the rat hippocampus (Folli et al 1994). The PI3K inhibitor LY294002 blocks learning and memory in mice (Barros et al 2001;Lin et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin receptors have also been identified in the DVC and a number of other caudal brainstem sites (e.g., 189,193). Like hypothalamic neurons bearing insulin receptors, those in the brainstem also are endowed with intracellular signaling substrates including insulin receptor substrate-1 and phosphatidylinositol 3-kinase (61). The consequences of brainstem insulin signaling to intake and body weight control have yet to be explored by 4th-icv or brainstem intraparenchymal administration studies.…”
Section: Insulinmentioning
confidence: 99%